Phytochemical screening and antimicrobial activity of extracts from leaves and stem of Ecbolium linneanum - Choudhury, Dipankar; Pathak, Arun K.; Sevanan, Murugan (Bangladesh Journal of Pharmacology, 2011)
The soxhlet extracts of leaves and stem of Ecbolium linneanum using different solvents were investigated for their phytochemical and antibacterial activity against pathogenic bacteria. Antibacterial activity was performed by using well agar and disc diffusion methods. Preliminary phytochemical screening revealed that leaves and stem contained various phytochemicals and were confirmed by spectroscopic methods. The bacterial pathogens were strongly inhibited by leaf extracts but acetone extracts of stem have failed to inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa even at the highest concentration. The results revealed that leaf extracts were found to be more effective than stem extracts. E. linneanum possesses antimicrobial activity against most commonly encountered human pathogens.